Foreigner in contemporary Japanese state discourse: Constructing differences between the nation and the Other - D. S. Alekseev (Японские исследования)
Researchers note that Japanese national identity has been shaped by the nihonjinron ideology, which defines the country as culturally unique and mono-ethnic, thus constituting a divide between Japan and the rest of the world. However, in the context of globalization, the Japanese government, following the global trend, has engaged in a national branding program called “Cool Japan,” which aims to attract foreigners and therefore differs in its message from nihonjinron. Previous research suggests that, in reality, Cool Japan is not so much in conflict with nihonjiron narratives, but rather inherits their rhetoric. However, little attention has been paid to how foreigners are represented within this program. Therefore, our research question is this: How is the interaction between the nation/national subjects and foreigners portrayed in the Cool Japan discourse, and what characteristics are attributed to both groups? Through narrative analysis and critical discourse analysis, this study examines government-affiliated media: articles from the “Friends of Japan” section in a government magazine and episodes from the NHK documentary series “Japanology Plus.” The findings show that the analyzed materials reproduce the boundaries between Japanese people and foreigners, rearticulate Japan’s cultural uniqueness, and implicitly reinforce the narrative of mono-ethnicity. In “Friends of Japan,” foreigners are portrayed as enthusiasts of Japanese culture, expected to mediate between Japan and the world without being fully integrated. Similarly, in “Japanology Plus,” foreigners are depicted as “Japanophiles,” helping to bridge Japan and the world by sharing Japan’s uniqueness. The position of foreigners in this discourse is ambivalent: they appear subordinate to Japanese nationals but are also seen as capable of revitalizing the country’s economy and are thus valued. This duality reflects Japan’s struggle to balance globalization with affirming national identity in the logic of nihonjinron, highlighting the challenges of integrating foreigners into Japanese society.